Three pebbles and a song - Spinelli, Eileen; Schindler, S. D. (New York : Dial Books for Young Readers, 2003)
As his mouse family endures a long, cold winter, Moses's contributions of a dance, a juggling act, and a little song prove more useful than he had supposed.
Wilson's Children.
School Library Journal.
Pub Weekly.
3.7
K-3
Keywords: Mice -- Juvenile fiction; Winter -- Juvenile fiction; Mice -- Fiction; Winter -- Fiction; Mice -- Fiction; Winter -- Fiction; Mice -- Fiction; Winter -- Fiction